Global environmental change and AIDS: Assessing effectiveness of food security interventions to multiple stresses in Zimbabwe - Drimie, Scott; Gandure, Sithabiso (International Food Policy Research Institute, 2008)
Global environmental change in Zimbabwe is intertwined with a challenging political environment, excessive economic decline, the depletion of scarce skills, and a generalized AIDS epidemic. Against this background, a development initiative known as the Protracted Relief Programme (PRP), led by the Food and Agricultural Organization of the United Nations (FAO) working with nongovermental organizations (NGOs) and supported by the Department for International Development (DFID), sought to build on and support existing livelihoods. This response was in contrast to the dominant form of external intervention—the distribution of food aid and the development of farming input schemes. The PRP targeted poor households by boosting their food production through promoting community gardens, conservation agriculture, seed multiplication, improving access to water, and providing care to the chronically ill.